PROFIL PRODUKSI DAN PETERNAK KEMITRAAN BROILER DI WILAYAH GERBANG KERTOSUSILA - Nonok Supartini; Hariadi Darmawan; Karunia Setyowati (BUANA SAINS, 2017)
The aim of this study are : (1) to identify production profile of broiler’s partnership at Gerbangkertosusila region; (2) to identify farmer’s profile of broiler’s partnership at Gerbangkertosusila region; (3) to identify human resources development factors of broiler’s partnership. This research done at Gerbangkertosusila region (Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo dan Lamongan) East Java Province for 2 (two) months. This research is quantitative research with Cross Sectional Survey which mean questionnaire method by question list used in order to data collected as primary and secondary data. Primary data collected by survey, observation and depth interviewed with questionnaire used in order to got valid data, such as farmer profile and production profile information. Secondary data collected by data study and documentation from government documents and broiler’s partnership corporation related documents. Data analysist was descriptive analysist. The conclusion of this study are : (1) Broiler’s farmer profile are mostly (90%) at productive ages with Senior High School graduated as the most common (75%) and an enterpreneur as main profession (45%) which more than 3 years of production periods (80%) and had experiences at 2 kind of broiler’s partnership models (60%); (2) Management contract as the most choosen broiler’s partnership models by respondents